Prediksi Financial Distress pada Perusahaan Sektor Pariwisata di Kabupaten Lombok Tengah Periode 2019-2020 - Nurkholik Iskandar; Herlina Pusparini; Nurabiah Nurabiah (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
This study aims to analyze and determine financial conditions as well as measure financial distress predictions for tourism service companies in Central Lombok district for the 2019-2020 period, namely the period before and at any time the covid-19 pandemic using the Modified Altman Z-score analysis method. The design of this research is descriptive research with data collection techniques through documentation. The data used are secondary data, financial statements of each company and the number of companies studied as many as three companies that are clients of DES Consultants. The data were analyzed using four X ratios defined by Altman and used to calculate the Z value of each company as a measuring tool to determine the level of health. The results of this study indicate that of the three companies analyzed, there is one company that is in financial distress, namely PT SWE Development Lombok. Meanwhile, two other companies, namely PT Serangan Indah Resort and PT Salt Lombok, are in the safe zone. Of the three companies, their Z-score values ​​both decreased in 2020. This is the effect of the covid-19 pandemic which caused the three difficulties in making a profit.